Clinical Profile and Outcome of Corona Virus Disease-19 Infection in Pregnant Women - Subedi, Kirtipal; Paudel, Prajwal; Thakur, Amitabh; Poudel, Sandesh; Sharma, Poonam; Adhikari, Shree Prasad (Journal of Nepal Health Research Council, 2022)
Background: The corona virus disease 19 pandemic has affected the whole world with pregnant ladies being more vulnerable population. This study aimed to evaluate characteristics of corona virus disease 19 infection in pregnancy and neonates and whether close proximity to the mother increases the incidence of corona virus disease infection in neonates..Methods: This is a hospital based prospective cross sectional observational study done among pregnant women presenting to Paropakar maternity and womens hospital from 1st September 2020 to 31st march 2021 with confirmed corona virus disease 19 infection. Results: The total 160 cases were included in study. Most of the women (33.8%) were of 20- 25 years of age, 55 % were multigravida and 77.6 % were full term. Around 74 % of cases were symptomatic with predominant symptoms being cough, fever and sore throat present in 33.1 %, 18% and 14% respectively. Out of 125 deliveries 71 % of cases underwent cesarean section of which fetal distress was most common indication. Six newborns were positive for corona virus disease 19 infection within 48 hours of life. Mortality was seen in four mothers and three neonates. Conclusions: The clinical presentation of corona virus disease infection in pregnant ladies is similar to general population. There is no increased risk of vertical transmission to the baby. Keywords: corona virus disease 19; pregnancy outcome; vertical transmission.